Quelques salons de Paris au XIIIe siecle - Filon, Marie 1842-1902 (Paris May, 1898)
Published in 1898, this book deals with the literary salons of eighteenth-century Paris. The author, Marie Filon pseudonym Mary Summer, describes the history of the salons, their places and personalities, and their influence on the intellectual and cultural life of France at the time.
Ouvrage orné de 10 portraits
Keywords: 18th Century (1701-1800); Salon; Cultural history; Paris (France)